Macassar fruit extract (Brucea javanica (l.) merr) increased the level of superoxide dismutase (SOD) but had no effect on the level of malondialdehyde (mda) in paraquat-treated male swiss Webster mice - Maria Eka Patri Yuliati; I Gusti Made Aman; Ni Nyoman Ayu Dewi (Fakultas Kedokteran Universitas Udayana, 2019)
Introduction: Paraquat exposure causes aging because it induces oxidative stress marked by decreased level of SOD and increased MDA serum level. Macassar fruit contains bioactive compounds such as vitamin C, flavonoids, tannins and polyphenol that have antioxidant activity. The purpose of this study was to prove that Macassar fruit extract increased the level of Superoxide Dismutase (SOD) enzyme and reduce the level of Malodialdehid (MDA) in male Swiss Webster mice treated by paraquat. Methods: A randomized pretest-posttest control group study was conducted using 14 male mice which were 2-3 months old, healthy and had 25-30 gram in weight. They divided into 2 groups namely P0 (control) and P1 (Treatment). Both groups were treated by paraquat but only group P1 received 20 mg Macassar fruit extract while the P0 only got 1 cc placebo for 14 days. Results: Our result showed that the level of SOD was increased in P1 group from 17.18±1.69 U/ml to 67.56±3.65 U/ml (p<0.01) while no change was observed in P0 group 16.97 ±1.45U/ml to 17.07±1.89 U/ml (p>0.05). However, no effect on MDA level was observed as the level of MDA tended to slightly decrease in both groups. Conclusion: It can be concluded that Macassar fruit extract 20 mg/kgBB significantly increased the level of SOD whilehave no effect on MDA level in male mice Swiss Webster treated by paraquat.